Building capabilities in disabled job seekers: A qualitative study of the Remploy Work Choices programme in Scotland - Peter J. Robertson (Social Work & Society, 2018)
This article reports on a qualitative study of the UK's labour activation pathway for jobseekers with disabilities and health conditions.  The aim was to explore the experiences of Work Choices programme participants, specifically to identify barriers to employment, the resources available to them, and the kind of support experiences they found empowering. Nine adult jobseekers took part in research interviews.  Accounts of their experience of the programme were recorded, transcribed, and analysed with Interpretative Phenomenological Analysis.  The Capability Approach of Amartya Sen was used as the conceptual lens through which the data was interpreted. Participants reported substantive health conditions, lack of skills and confidence, and practical obstacles to finding work. They valued being treated with dignity, having genuine choice about their work and learning options, and experiencing a service underpinned by a supportive helping relationship.